1988
DOI: 10.1161/01.cir.77.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Sequential thallium-201 myocardial perfusion studies after successful percutaneous transluminal coronary artery angioplasty: delayed resolution of exercise-induced scintigraphic abnormalities.

Abstract: To characterize the sequential changes of myocardial perfusion scintigraphy in patients with coronary artery disease (CAD) after complete revascularization, 43 patients undervwent exercise thallium-201 (201T1) myocardial perfusion scintigraphy before and at 9 5 days, 3.3 ± 0.6, and 6.8 -+ 1.2 months after percutaneous transluminal coronary angioplasty (PTCA). Only patients with single-vessel CAD, without previous myocardial infarction, and without evidence of restenosis at 6 to 9 months after PTCA were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
7

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(37 citation statements)
references
References 42 publications
0
30
0
7
Order By: Relevance
“…The presence of early reversible perfusion defects predicted late coronary restenosis [4, 5, 6]. In some patients, reversible perfusion defects resolved in the months following the procedure [15]. …”
Section: Discussionmentioning
confidence: 99%
“…The presence of early reversible perfusion defects predicted late coronary restenosis [4, 5, 6]. In some patients, reversible perfusion defects resolved in the months following the procedure [15]. …”
Section: Discussionmentioning
confidence: 99%
“…In the era of coronary angioplasty, many studies reported that numerous "false positive" reversible perfusion defects occurred early after angioplasty, possibly as a result of inadequate early vessel remodeling or sustained abnormalities of coronary vasomotor tone. However, a significant percentage of patients showed persistent abnormalities in the later period [59][60][61][62][63][64][65][66] . In one study, 76% of patients without prior myocardial infarction showed improvement in perfusion abnormalities after angioplasty, but only 34% had completely reversible ischemia [60] .…”
Section: Mortality?mentioning
confidence: 99%
“…Non- invasive diagnosis of restenosis can be challenging. Previous SPECT studies have demonstrated that normalization of regional myocardial perfusion usually occurs after successful revascularization (Manyari et al, 1988;Zhang et al, 2004). In a follow-up study using quantitative contrast stress echocardiography in 33 patients with stable angina pectoris treated with percutaneous coronary intervention and stent implantation, there was no improvement in stress-induced myocardial perfusion during follow-up in patients who had developed a significant angiographic restenosis, while the stress-induced perfusion was improved in patients with successful revascularisation at 9 months .…”
Section: Restenosis After Revascularizationmentioning
confidence: 99%